Evaluation of competitiveness at county level, by urban-rural typology - Mihai Alexandru Chiţea (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The main objective of the present paper was the evaluation of the overall performance of the territorial units, at county level, expressed through competitiveness, based on an evaluation model designed specifically for this aggregation level. The theoretical model was elaborated taking into account the specific literature regarding the territorial competitiveness, that highlighted the need for further development at local level, which in our case is represented by the county level. Furthermore, the analysis focused on the results based on the urban-rural typology, that pointed out some differences between the competitiveness level, namely a lower level in the case of predominantly rural regions, compared to the intermediate and predominantly urban ones.
Keywords: O18; 330; territorial competitiveness; county level; urban-rural typology